Citizenship and social security of landless Dalits in Nepal - Tilak Biswakarma (Globe, 2018)
The intertwined relationship between rights and responsibilities are reciprocal between people and the State. Citizenship and land ownership are fundamental means through which people's relationship with the State is adjudged and determined. The study explores how the lack of accessibility of land ownership and citizenship certificate affects peoples' civil, political and social rights. The same is concluded through the case study of landless Dalits. To factor the relationship between landlessness, citizenship and social security; unstructured interviews with 60 household heads were conducted. The study found that the lack of citizenship certificate and land ownership certificate promotes the feeling of statelessness, without a change in patriotic impulse. Despite the government’s attempts to redistribute land in the area, the gradients of socio-economic and political power determine the fate of landless Dalits. The Dalits, inept and minority stakeholders, continue to be landless after more than four decades, whereas the elites are able to obtain land ownership certificate through their influence on the local authorities. Landless Dalits are being ignored not only by the State and political parties, but also by national and international organizations. Discriminatory behaviour of the State towards Dalits is an ongoing process without the provision of basic fundamental rights. This has affected their sense of citizenship.